Glycolysis and beyond in glucose metabolism: exploring pulmonary fibrosis at the metabolic crossroads - Wang, Yuejiao; Wang, Xue; Du, Chaoqi; Wang, Zeming; Wang, Jiahui; Zhou, Nan; Wang, Baohua; Tan, Ke; Fan, Yumei; Cao, Pengxiu (Frontiers in Endocrinology, 2024)
At present, pulmonary fibrosis (PF) is a prevalent and irreversible lung disease with limited treatment options, and idiopathic pulmonary fibrosis (IPF) is one of its most common forms. Recent research has highlighted PF as a metabolic-related disease, including dysregulated iron, mitochondria, lipid, and glucose homeostasis. Systematic reports on the regulatory roles of glucose metabolism in PF are rare. This study explores the intricate relationships and signaling pathways between glucose metabolic processes and PF, delving into how key factors involved in glucose metabolism regulate PF progression, and the interplay between them. Specifically, we examined various enzymes, such as hexokinase (HK), 6-phosphofructo-2-kinase/fructose-2,6bisphosphatase 3 (PFKFB3), pyruvate kinase (PK), and lactate dehydrogenase (LDH), illustrating their regulatory roles in PF. It highlights the significance of lactate, alongside the role of pyruvate dehydrogenase kinase (PDK) and glucose transporters (GLUTs) in modulating pulmonary fibrosis and glucose metabolism. Additionally, critical regulatory factors such as transforming growth factor-beta (TGF-β), interleukin-1 beta (IL-1β), and hypoxia-inducible factor 1 subunit alpha (HIF-1α) were discussed, demonstrating their impact on both PF and glucose metabolic pathways. It underscores the pivotal role of AMP-activated protein kinase (AMPK) in this interplay, drawing connections between diabetes mellitus, insulin, insulin-like growth factors, and peroxisome proliferator-activated receptor gamma (PPARγ) with PF. This study emphasizes the role of key enzymes, regulators, and glucose transporters in fibrogenesis, suggesting the potential of targeting glucose metabolism for the clinical diagnosis and treatment of PF, and proposing new promising avenues for future research and therapeutic development.